Flexible Electronic Substrate Film Fabricated Using Natural Clay and Wood Components with Cross‐Linking Polymer. Issue 17 (1st March 2017) - Takahashi, Kiyonori; Ishii, Ryo; Nakamura, Takashi; Suzuki, Asami; Ebina, Takeo; Yoshida, Manabu; Kubota, Munehiro; Nge, Thi Thi; Yamada, Tatsuhiko
Abstract : Requirements for flexible electronic substrate are successfully accomplished by green nanocomposite film fabricated with two natural components: glycol‐modified biomass lignin and Li + montmorillonite clay. In addition to these major components, a cross‐linking polymer between the lignin is incorporated into montmorillonite. Multilayer‐assembled structure is formed due to stacking nature of high aspect montmorillonite, resulting in thermal durability up to 573 K, low thermal expansion, and oxygen barrier property below measurable limit. Preannealing for montmorillonite and the cross‐linking formation enhance moisture barrier property superior to that of industrial engineering plastics, polyimide. As a result, the film has advantages for electronic film substrate. Furthermore, these properties can be achieved at the drying temperature up to 503 K, while the polyimide films are difficult to fabricate by this temperature. In order to examine its applicability for substrate film, flexible electrodes are finely printed on it and touch sensor device can be constructed with rigid elements on the electrode. In consequence, this nanocomposite film is expected to contribute to production of functional materials, progresses in expansion of biomass usage with low energy consumption, and construction of environmental friendly flexible electronic devices. Abstract : A flexible electronic device with rigid elements is successfully constructed on nanocomposite film consisting of natural clay, lignin derivative, and cross‐linking polymer. Several requirements for flexible substrate can be accomplished excellently by using Li + montmorillonite clay and a cross‐linking reaction between a lignin derivative and an acrylic polymer with oxazoline side chains.